Lung Ultrasound Characteristics in Neonates With Positive Real Time Polymerase Chain Reaction for SARS-CoV-2 on a Tertiary Level Referral Hospital in Mexico City - Daniel Ibarra-Ríos; Andrea Constanza Enríquez-Estrada; Eunice Valeria Serpa-Maldonado; Ana Luisa Miranda-Vega; Dina Villanueva-García; Edna Patricia Vázquez-Solano; Horacio Márquez-González (Frontiers Media S.A., 2022)
IntroductionAcute respiratory syndrome secondary to SARS-CoV-2 virus infection has been declared a pandemic since December 2019. On neonates, severe presentations are infrequent but possible. Lung ultrasound (LUS) has been shown to be useful in diagnosing lung involvement and following up patients, giving more information, and reducing exposure compared to traditional examination.MethodsLUS was performed after the diagnosis of SARS-CoV-2 infection with respiratory Real Time Polymerase Chain Reaction RT-PCR with portable equipment protected with a silicone sleeve. If hemodynamic or cardiology consultation was necessary, a prepared complete ultrasound machine was used. Ten regions were explored (anterior superior and inferior, lateral, and posterior superior and inferior, right and left), and a semiquantitative score (LUSS) was calculated. Disease severity was determined with a pediatric modified score.ResultsThirty-eight patients with positive RT-PCR were admitted, 32 (81%) of which underwent LUS. Included patients had heterogenous diagnosis and gestational ages as expected on a referral neonatal intensive care unit (NICU) (median, ICR: 36, 30-38). LUS abnormalities found were B-line interstitial pattern 90%, irregular/interrupted/thick pleural line 88%, compact B-lines 65%, small consolidations (≤5 mm) 34%, and extensive consolidations (≥5 mm) 37%. Consolidations showed posterior predominance (70%). LUSS showed a median difference between levels of disease severity and ventilatory support (Kruskal-Wallis, p = 0.001) and decreased with patient improvement (Wilcoxon signed-rank test p = 0.005). There was a positive correlation between LUSS and FiO2 needed (Spearman r = 0.72, p = 0.01). The most common recommendation to the attending team was pronation (41%) and increase in positive end expiratory pressure (34%). Five patients with comorbidities died. A significant rank difference of LUSS and FiO2 needed between survivors and non-survivors was found (Mann-Whitney U-test, p = 0.005).ConclusionLUS patterns found were like the ones described in other series (neonatal and pediatrics). Eighty-eight percent of the studies were performed with handheld affordable equipment. While there is no specific pattern, it varies according to gestational age and baseline diagnosis LUS, which were shown to be useful in assessing lung involvement that correlated with the degree of disease severity and respiratory support.